Kansas and Kansans in World War I : service at home and abroad - Watson, Blake A., 1956- (University Press of Kansas, 2024)
"According to the American Battle Monuments Commission, approximately 80,000 Kansans served in the US armed forces during World War I. In Kansas and Kansans in World War I, Blake Watson helps readers understand how World War I affected Kansas and its residents, and how Kansans in turn had an impact on the outcome of the Great War. Through thorough and extensive use of letters, newspapers, and other documents, Watson brings individual soldiers' service to life, using their own words to describe their attitudes and experiences. Watson also looks at Kansans' service and support on the home front, chronicling Kansans' participation in initiatives such as Liberty Loan bonds, newspapers' publication of military service honor rolls and soldiers' letters from abroad, and the xenophobia and hysteria that confronted Mennonites--who were pacifists--and German Americans"--